Anomalous coloration of a yellow tail damselfish Stegastes arcifrons (Actinopterygii: Pomacentridae) at Isla del Coco National Park, Costa Rica - Beita-Jiménez, Andrés; Alvarado, Juan José (Revista de Biología Tropical, 2016)
Coloration patterns of reef fishes are an important trait for mediating intra and interspecific interactions, as well as for taxonomic identifications. Here we report a specimen of Stegastes arcifrons that presented a previously unobserved and anomalous color variation on a coral reef at Isla del Coco, Pacific Costa Rica. This color variation is known as xanthism and has been reported in some damselfishes, usually associated with genetic anomally.